Upaya Peningkatan Kreativitas Melukis dengan Media Karet Gelang pada Anak Kelompok B TK Kemala Bhayangkari 70 Masaran - Martini, Tri (Didaktika, 2023)
Activities at Kemala Bhayangkari 70 Masaran Kindergarten still used conventional painting media using crayons. Initial observations show that learning activities are less attractive to children, activities are less varied monotonous, and learning is more often carried out in the classroom so that the space for children to move is less free, resulting in creativity that does not look optimal. Rubber bands have the potential to become a medium for children's painting activities in kindergarten because children often find them and are often used by children to play. This classroom action research was carried out at Kemala Bhayangkari 70 Masaran Kindergarten in the Odd Semester of the 2022/2023 Academic Year with the research subject being group B students with a total of 31 children consisting of 16 boys and 15 girls. In this research, the independent variable is creativity in painting with indicators of fluency, authenticity, detail, neatness, harmony. The data collection methods used are observation and documentation. After the researcher held the first cycle by applying the rubber band media, it was obtained that in the first cycle, it increased by 71.67% with the criteria of Developing as Expected (BSH). But the results obtained have not been maximized because they have not reached the mutually agreed success indicator of 80%. For this reason, researchers and collaborating partners held cycle II, with the same learning and activities with a variety of varied color choices. The results achieved in research in cycle II the average percentage of children in 1 class was 84.73% with the Very Well Developed (BSB) assessment criteria. The data shows that children's creativity has increased, for this reason, researchers have succeeded and achieved mutually agreed indicators and it is proven that painting with rubber band media can increase the creativity of Kemala Bhayangkari 70 Kindergarten children  Masaran